2019
DOI: 10.1021/acs.jpclett.9b00333
|View full text |Cite
|
Sign up to set email alerts
|

Acid–Amine Equilibria for Formation and Long-Range Self-Organization of Ultrathin CsPbBr3 Perovskite Platelets

Abstract: Impact of acid–amine equilibrium for triggering the formation of CsPbBr3 platelets and subsequent long-range self-assembly as a function of acid concentration is reported. The study was performed by treating Cs precursor followed by oleic acid to the ongoing process of L2PbBr4 layered perovskites formation at room temperature, and this led to the thinnest possible platelets of CsPbBr3 with one atomic layer of Cs insertion. These platelets form self-assembly in the micrometer range, and this ordering was tuned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 48 publications
9
49
0
Order By: Relevance
“…In addition, the growth of Cs‐based LHP NPL can be accelerated by heating. Similarly, in a previous study, slow reaction kinetics in CsPbBr 3 NPLs were observed by Mehetor et al [35] . The narrowest emission linewidth was observed in L 2 [FAPbX 3 ]PbX 4 NPLs as shown in Figure 4c.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, the growth of Cs‐based LHP NPL can be accelerated by heating. Similarly, in a previous study, slow reaction kinetics in CsPbBr 3 NPLs were observed by Mehetor et al [35] . The narrowest emission linewidth was observed in L 2 [FAPbX 3 ]PbX 4 NPLs as shown in Figure 4c.…”
Section: Resultssupporting
confidence: 85%
“…Additionally, powder XRD patterns of L 2 [APbX 3 ]PbX 4 samples were shown in Figure S3. Periodic peaks in the XRD pattern indicate 4.3 nm stacking distance between NPL superstructure [18,35,44] . The STEM images in Figure 2f and g reveal that the nanoparticles are of platelet morphology.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Note that the interplanar spacing equals the NPLs thickness plus the two times length of the oleic acid ligand (≈1.5 nm) on each side of the single NPL, and the NPLs thickness can be approximated as n × 0.6 nm, where n represents the layer number of 2D arrangement of corner‐sharing [PbBr 6 ] 4− octahedra with a thickness of ≈0.6 nm. [ 13 ] Therefore, the measured stacking distance of ≈4.1 nm manifests an average NPL thickness of ≈1.1 nm, corresponding to approximately two monolayers of [PbBr 6 ] 4− octahedra. Consistently, the TEM images showing stacked CsPbBr 3 NPLs standing on their edges give an estimated thickness of a single NPL as ≈1.4 nm (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
“…Specifically, OnA can form a chelate with Sb 3+ metal ions whereas OAm can stabilize the resulting NC and NW formation. The morphology of Cs 3 Sb 2 Br 9 NCs in terms of NCs and NWs can be tuned by varying the proportion of ligands and the selective precipitation [19]. FTIR spectroscopy showed the presence of OAm, OnA, and OA on the surfaces of the Cs 3 Sb 2 Br 9 NCs (Figure 1c).…”
Section: Resultsmentioning
confidence: 99%